Design of a fault tolerant control systems for hazardous chemical injection in a gas manufacturing plant - Ang, Lian Peng (2008)
This project aims to design a suitable chemical injection system for odorant injection into a pressurized gas mixer to stench manufactured gas. The odor intensity is controlled by a ratio control scheme.